The sense of coherence and resilience of HIV-positive students in the support group of a university in the Eastern Cape - Hoho, Veliswa Nomfundu (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2014.